Quantifying the Terrestrial Carbon Feedback to Anthropogenic Carbon Emission. Issue 12 (26th December 2019) - Goodwin, Philip
Abstract: The surface warming response to carbon emission is dependent on feedbacks operating in both the physical climate and carbon cycle systems, with physical climate feedbacks quantified via linearly combinable climate feedback terms, λ climate in watt per square meter per kelvin. However, land carbon feedbacks are often quantified using a two‐parameter description, with separate cumulative carbon uptake responses to surface warming, γ L in petagram of carbon per kelvin, and rising atmospheric CO2 concentration, β L in petagram of carbon per parts per million. Converting the γ L and β L responses to an overall terrestrial carbon feedback parameter, λ carbon in watt per square meter per kelvin, has remained problematic, with λ carbon affected by significant nonlinear interactions between carbon‐climate and carbon‐concentration responses and a nonlinear relation between atmospheric CO2 and subsequent radiative forcing. This study presents new relationships quantifying how the overall steady state terrestrial carbon feedback to anthropogenic emission, λ carbon, is dependent on the terrestrial carbon responses to rising CO2 and temperature, β L, and γ L, and the physical climate feedback, λ climate . Nonlinear interactions between β L and γ L responses to carbon emission are quantified via a three‐parameter description of the land carbon sensitivities to rising CO2 and temperature. Numerical vegetation model output supports the new relationships, revealing an emerging sensitivity of land carbon feedback to climate feedback of ∂ λ carbon /∂ λ climate 0.3. The results highlight that terrestrial carbon feedback and physical climate feedback cannot be considered in isolation: Additional surface warming from stronger climate feedback is automatically compounded by reduced cooling from terrestrial carbon feedback, meanwhile around half the uncertainty in terrestrial carbon feedback originates from uncertainty in the physical climate feedback. Plain Language Summary: The amount of surface warming caused by carbon emission is influenced by feedback processes operating in both the physical climate system and in the carbon cycle. Physical climate feedbacks include the responses of clouds, snow and ice cover, atmospheric water vapor, and atmospheric lapse rate properties to surface warming. Each of these physical climate feedbacks affects how much warming is generated from a rise in atmospheric carbon dioxide. In contrast carbon cycle feedbacks work in a very different way: By affecting how much of the emitted carbon dioxide is taken up by the land and ocean systems, carbon cycle feedbacks affect how much atmospheric carbon dioxide rises in response to human carbon emission. Since they work in different ways, it has been difficult to directly compare the strengths of physical climate feedbacks with carbon cycle feedbacks. This study identifies a new way of quantifying steady state land carbon cycle feedbacks so that they are easily compared to physical climate feedbacks. A link is also found identifying how land carbon feedbacks remove less carbon dioxide from the atmosphere if physical climate feedbacks cause more warming. In this way, the land carbon feedback could increase additional warming from strong physical climate feedbacks. Key Points: New relationship converts carbon‐concentration and carbon‐climate response into land carbon feedback, comparable to climate feedback Emergent link identified between strengths of land carbon feedback and physical climate feedback in response to anthropogenic forcing Around half the uncertainty in land carbon feedback originates from uncertainty in physical climate feedback